2019
DOI: 10.1021/acs.jpcc.9b04731
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hydroxyl Species in Hydrogen Oxidation Reaction: A DFT Study

Abstract: Slow kinetics of the hydrogen oxidation reaction (HOR) in alkaline electrolyte impedes the development of alkaline fuel cell systems. In this work, density functional theory calculations were used to study the HOR mechanism on several metals (Pt(110), Ir(110), Pd(110), Ni(110), and PtRu(110)), particularly by additionally considering the adsorption of hydroxyl species (OH*) on these metals. We found that the formation of OH* can transfer the potential-determining step of HOR mechanism from the H* oxidation to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 53 publications
3
44
0
Order By: Relevance
“…The activity of each of the two types of MCS was studied by LSV in M NaClO 4 solutions under various pH conditions (from pH 8 to pH , Ar atmosphere), so as to be able to compare our findings with those reported previously [ 27 , 43 ]. As expected [ 22 , 27 , 40 ], we found that the oxidation process occurs at pH > 10, and that the oxidation current and potential depend both on the pH and on the pattern pitch dimension ( Figure 3 ). The waves between ∼ V (depending on the conditions) are attributed to the oxidation of Ni(OH) 2 through Reaction ( 3 ).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The activity of each of the two types of MCS was studied by LSV in M NaClO 4 solutions under various pH conditions (from pH 8 to pH , Ar atmosphere), so as to be able to compare our findings with those reported previously [ 27 , 43 ]. As expected [ 22 , 27 , 40 ], we found that the oxidation process occurs at pH > 10, and that the oxidation current and potential depend both on the pH and on the pattern pitch dimension ( Figure 3 ). The waves between ∼ V (depending on the conditions) are attributed to the oxidation of Ni(OH) 2 through Reaction ( 3 ).…”
Section: Resultssupporting
confidence: 88%
“…We show that MCS electrode can efficiently oxidize water and increase the efficiency of the WSP. The use of DPN to generate the electrode, demonstrated here for the first time, is considerably simpler than other methods [ 20 , 22 , 26 , 27 ]. It enables the patterning of uniform nanoclusters of OER catalysts, such that the process can be controlled by changing the solution pH, the size of the clusters, and the pattern pitch dimensions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 49–53 ] Besides, Wei and co‐workers studied the role of OH* in the HOR on Pt(110), Ir(110), Pd(110), Ni(110), and PtRu(110) using density functional theory (DFT) calculations. [ 54 ] The authors found that OH* adsorption induces remarkably different effects on H* and adsorbed water molecule (H 2 O*), and the combination of Δ G OH* , Δ G H* , and Δ G H2O* should be evaluated altogether to achieve a more precise and comprehensive understanding on the HOR/HER mechanism. Jia and co‐workers proved that the alkali metal cations (AM + ) including Li + , Na + , K + , Rb + , and Cs + destabilize the OH* in the electric double layer by forming the OH − ‐(H 2 O) x ‐AM + adducts, [ 55 ] which is detrimental to the HOR based on the bifunctional mechanism.…”
Section: Hor Mechanismmentioning
confidence: 99%
“…Calculation of the H2 molecule was obtained by placing the atom in a 1 nm cube. To obtain the Gibbs Free Energy profiles of the HOR at 0 V and equilibrium potential, we followed the thermodynamic pathways of the HOR as described in the work of Wei and co-workers 30 . The Open Visualization Tool (OVITO) 31 was used to visualize all the configurations and models.…”
Section: Synthesis Of Electrocatalystsmentioning
confidence: 99%